QARAQALPAQ XALÍQ DÁSTANÍ «SHÁRYAR»: JIYNALÍWÍ, BASÍP SHÍǴARÍLÍWÍ HÁM IZERTLENIWINIŃ AYÍRÍM MÁSELELERI - Keńesbaeva, Sh.K. (SCIENCE and SOCIETY, 2019)
The article deals with the genre peculiarities of the Karakalpak folklore epos «Shariyar», the other peoples don't have the analogy to it. The author of the article compares different points of view on this issue in Karakalpak folklore and comes to the concuision that this epos is neither social-realistic, nor a work with an external plot, but it is a mythologic-fairy tale epos.
Keywords: the degree of the study of the problem the epos «Shariyar»; genre peculiarities; an epos with external plot (O.Kojurov); social-realistic epos (K.Maksetov); a fairy-tale epos (I.Sagitov); a fairy tale motive; myth motive; myth-fairy tale epos; the problems and solutions of study of epos